Three new species of the leafhopper genus Pedionis Hamilton (Hemiptera: Cicadellidae: Macropsinae) from China - Dai, Ren-Huai; Li, Hu (Zootaxa, 2012)
Three new species, Pedionis (Pedionis) acerosa sp. nov., P. (P.) longiaxonica sp. nov. and P. (P.) obtusata sp. nov. from China, are described and illustrated. A key is given to distinguish all species of the genus from China.